"We Meet Them and Treat Them as Brethren": Nativists and Republican Appeasement - Widener, Mitchell J. (Kansas State University. Dept. of History, 2012)
“We Meet Them and Treat Them as Brethren”: Nativists and Republican Appeasement Author: Mitchell J. Widener The American Party reached its zenith in 1856 when it elected members to local and federal positions and nominating ex-President Millard Fillmore as its presidential candidate. By 1860, this nativist party was essentially defunct. That same year marked the fusion of the Republican Party with the northern American Party members. The process by which the nativists joined the Republican Party presents historians with many problems. Recently, many historians contend the GOP absorbed the nativists without making any concessions to them at the state or federal level. However, through a close examination of northern state political record’s, this paper will argue Republicans gained northern nativist votes by making concessions to them at the state rather than the national level. Specifically, New York, Massachusetts, Ohio, Pennsylvania, and Michigan’s state records will be analyzed. Among other things, many states passed voter registry laws to curb the voting rights of immigrants. This becomes important if one wishes to gain a better understanding of Lincoln and the Republican’s rise to power in the late 1850s.
Keywords: Nativism; Republicans; State Politics 1850s; Know Nothings